CHARACTERIZATION TEST OF BINAHONG (ANREDERA CORDIFOLIA (TEN.) STEENIS.) LEAVES AND ALOE VERA (ALOE VERA) LEAVES EXTRACTS USING INFUDATION METHOD IN MAKING LIQUID FOR EXTERNAL WOUND HEALING - Ahmad Shobib; Priyono Kusumo; Nurul Millah (Universitas Wahid Hasyim, 2022)
Binahong leaves and aloe vera leaves contain flavonoid compounds and saponin compounds that can help the wound healing process, therefore a liquid medicine for external wound healing is made from extracts of binahong leaves and aloe vera leaves. The process of making liquid medicine begins with the manufacture of binahong leaf extract using binahong leaves carried out by the infundation method. The infundation method was carried out through an extraction process using distilled water at a temperature of (80-90)oC for 15 minutes. The results of the hypothesis show that at a temperature of (80-90)oC for 15 minutes there are no variables that affect the manufacture of binahong leaf extract. The binahong leaf extract and aloe vera were mixed according to the specified formula. The formulation used was the ratio (binahong leaf extract: aloe vera leaf) = 1:1 as formula A; 1:2 as formula B; 2:1 as formula C; 1.5:1 as formula D and added alcohol in the ratio (alcohol: a mixture of binahong leaf extract and aloe vera leaf) 1:4 to prevent oxidation. The preparation obtained is liquid so that it is easier to apply. The test results showed that the external wound healing liquid formulation with a volume ratio of aloe vera leaf extract and binahong 2:1 (Formulation C = 1.8467%) showed a high flavonoid content compared to formulas A, B, or D. The chosen method is that every 1 L of external wound healing liquid medicine consists of 536 ml of binahong leaf extract, 268 ml of aloe vera leaf extract, 201 ml of 70% alcohol from the total volume